Targeting vascular endothelial growth factor in renal cell carcinoma. - Patel, N; Muneer, A; Blick, C; Arya, M; Harris, A (2009)
Renal cancer is the most lethal of all urological malignancies with overall 5-year survival rates of around 60%. The predominant reason for the poor prognosis of this cancer has been the relative lack of effective systemic therapy for advanced metastatic disease. Until recently immunotherapy with interleukin-2 or interferon-alpha has been the standard of care for metastatic renal cell carcinoma (RCC); however, the response rates for these treatments were at best only 3-21%. The use of molecular biological techniques has led to a greater understanding of the genetic basis of RCC. Mutations of the von Hippel-Lindau (VHL) gene on chromosome 3p25 with the resultant overexpression of hypoxia-inducible factors (HIFs) have been shown to lead to the development of clear-cell RCC. The unearthing of the pathways downstream of VHL has led to the development of numerous novel therapies that specifically target HIF-related genes such as vascular endothelial growth factor (VEGF). In this article, we explore the VHL-HIF-VEGF pathway that plays a fundamental role in the development of renal cancer. In addition, we review the evidence base for the use of these new targeted therapies for advanced RCC and uniquely include the latest practice guidelines from the European Association of Urology, the United States National Comprehensive Cancer Network and the National Institute for Health and Clinical Excellence.